Therapeutic potential of Gynura procumbens in obesity, metabolic syndrome, and diabetes - Husak, Viktor; Shvadchak, Volodymyr; Sheremeta, Lidiia; Abrat, Oleksandra (Journal of Vasyl Stefanyk Precarpathian National University. Biology, 2024)
The growing global burden of obesity, metabolic syndrome, and diabetes has led to increased interest in alternative treatment methods due to the limitations of conventional therapy, including side effects, high cost, limited long-term effectiveness, and psychological factors. As a result, researchers are increasingly turning to the search for alternative natural compounds that can provide safe and effective treatment for metabolic disorders. Among plant-based compounds, Gynura procumbens, a traditional medicinal plant from Southeast Asia used for the prevention and treatment of various diseases, including metabolic disorders, has garnered particular attention. This review examines the therapeutic potential of G. procumbens ("longevity spinach"), a traditional medicinal plant from Southeast Asia, in the treatment of obesity, metabolic syndrome, and diabetes. The plant is rich in bioactive compounds, including flavonoids, saponins, tannins, and phenolic acids, that have the ability to influence key metabolic pathways associated with the regulation of glucose, lipid, and blood pressure levels. Recent studies shows that G. procumbens extracts have a positive impact on reducing blood glucose levels, improving insulin resistance, regulating the lipid profile, and promoting weight loss, as well as reducing oxidative stress and suppressing inflammatory processes in animal models, which holds promise for further application in the treatment of metabolic disorders. Analyzing recent literature on animal model experiments and some preclinical and clinical trials, this review evaluates the plant's phytochemical profile, mechanisms of action, physiological effects, and safety aspects. Particular attention should be paid to determining the optimal dose, treatment duration, and potential side effects and interactions with other medications that may be used by patients. Thus, G.procumbens has the potential to become an important component in comprehensive therapeutic strategies for the treatment of obesity, diabetes, and metabolic syndrome, but further research is necessary to confirm its clinical value definitively and identify the particular active compounds.